2023
DOI: 10.1097/hep.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth interventions in patients with chronic liver diseases: A systematic review

Abstract: Background and Aim: Telehealth interventions may improve access to care, disease-specific, and quality outcomes in chronic liver diseases (CLDs). We aimed to systematically evaluate outcomes of telehealth interventions in CLDs. Materials and Methods: We used key terms and searched PubMed/ EMBASE from inception to January 10, 2022. Two authors independently screened abstracts. Disagreements were resolved by a third reviewer. We included any type of CLD, including posttransplant patients, and extracted outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…[9] TM has also made its way into the transplant referral process; a recent systematic review of TM interventions in patients with CLD identified 8 studies reporting on TM-related liver transplantation referrals, evaluations, and listings demonstrating both decreased time from referral to evaluation and listing. [10] The benefits of TM are apparent; it can improve and optimize access to medical care for disadvantaged patient populations, reduce patient travel, and expedite care for patients with CLD. The limitations include (a) difficulty in navigating TM for older adults due to media device literacy, (b)access to the internet, and (c) uncertainty regarding insurance reimbursement for the services provided.…”
Section: Telemedicine In the Care Of Patients With Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…[9] TM has also made its way into the transplant referral process; a recent systematic review of TM interventions in patients with CLD identified 8 studies reporting on TM-related liver transplantation referrals, evaluations, and listings demonstrating both decreased time from referral to evaluation and listing. [10] The benefits of TM are apparent; it can improve and optimize access to medical care for disadvantaged patient populations, reduce patient travel, and expedite care for patients with CLD. The limitations include (a) difficulty in navigating TM for older adults due to media device literacy, (b)access to the internet, and (c) uncertainty regarding insurance reimbursement for the services provided.…”
Section: Telemedicine In the Care Of Patients With Cirrhosismentioning
confidence: 99%
“…A large observational study of Veterans Affairs population with CLD enrolled in Specialty Access Network‐Extension of Community Healthcare Outcome (the SCAN‐ECHO) study showed decreased risk of mortality in 518 patients compared to 62,237 controls with no visits (HR of 0.54 [95% CI: 0.36–0.81, p = 0.003]) 9 . TM has also made its way into the transplant referral process; a recent systematic review of TM interventions in patients with CLD identified 8 studies reporting on TM-related liver transplantation referrals, evaluations, and listings demonstrating both decreased time from referral to evaluation and listing 10 …”
Section: Telemedicine In the Care Of Patients With Cirrhosismentioning
confidence: 99%
“…Telehealth platforms often enable patients open up to express their needs while on therapy in and out of the treatment center. The multidisciplinary team members could also monitor the patient's clinical and psychological status by sharing signs and symptoms from the patient to healthcare providers [56][57][58].…”
Section: Multidisciplinary Approach In the Management Of Cancermentioning
confidence: 99%